Pancasila as Law Enforcement Ethics - Bagas Setyo Nugroho; Nurul Muarifah; Terysa Puji Rahayu; Riska Andi Fitriono (Journal of Education Technology Information Social Sciences and Health, 2022)
Pancasila is not only a source of derivation of legislation, but also a source of morality, especially in relation to the legitimacy of power, law and various policies in the implementation and administration of the state. The existence of the first precept of “The Almighty Godhead”, and the second precept of “Fair and Civilized Humanity” is the source of moral values for national and state life. The state of Indonesia which is based on the first precept of “The Almighty God” is not a “theocracy” state which bases state power and state administration on religious legitimacy. The power of the head of state is not absolute based on religious legitimacy but based on legal legitimacy and democratic legitimacy. Therefore, the principle of the principle of “Godhead of the Almighty” has more to do with moral legitimacy. This is what distinguishes the Almighty God from theocracy. The writing method in this journal is a qualitative method, with an interdisciplinary approach. Although in the Indonesian state it is not based on religious legitimacy, morally the life of the state must be in accordance with the values derived from God, especially the law and morals in the life of the state.